Isolation and Characterization of Bioemulgent from the fruit pulp of Prunus insititia - Bansal, Abhishek; Madhav, NV Satheesh; Sharma, AK (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The aim of the research work was to isolate biopolymer and to evaluate its emulsifying ability by formulating o/w type of emulsion. The biopolymer was isolated from the fruit pulp of Prunus insititia by treating with water. The aqueous extract was treated with an optimized ratio of dimethyl ketone and kept in refrigeration for 6 hours. The biopolymer was collected by centrifugation, dried and subjected to physicochemical analysis like solubility, pH, colour, viscosity. Eight different emulsions of o/w type were prepared by using liquid paraffin oil and biopolymer in various concentrations ranging from 50 mg to 1 gm. The formulated emulsions were subjected for various evaluation parameters like globule size, pH, the effect of freezing and thawing cycle, effect of centrifugation, etc. The results were compared with the standard emulsion which was prepared by using acacia as an emulsifier. The emulsions were not showing any significant stability due to increase in the globule size. The final conclusion can be drawn that the biopolymer as an emulsifier in lower concentration (50 and 100 mg) showed its potential emulsifying property in the formulation FE1 and FE2 with uniform globule size ranging from 12 to 30 ?m and stable for 3 freezing and thawing cycles. Dhaka Univ. J. Pharm. Sci. 14(1): 1-9, 2015 (June)